Chrysene-based blue emitters - Nathusius, Marvin; Ejlli, Barbara; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F.; Müllen, Klaus (Chemistry - a European journal, 2020)
Chrysene and its bisbenzannulated homologue, naphtho[2,3-c]tetraphene, were synthesized through a PtCl2-catalyzed cyclization of alkynes, which also furnished corresponding biaryls subsequent to a Glaser coupling reaction of the starting alkynes. The optoelectronic properties of 5,5′-bichrysenyl and 6,6′-binaphtho[2,3-c]tetraphene were compared to their chrysene-based “monomers”. Oxidative cyclodehydrogenations of bichrysenyl and its higher homologue towards large nanographenes were also investigated.
Gesehen am 26.08.2024